Is Moral Criticism of Law Possible? - Marcheva, Deyana (Yearbook of the Law Department, 2022)
In this article I represent the project for moral criticism of law, as developed by Robin West in “Narrative, Law and Authority”. I analyse how the issue of moral criticism of law comes to the fore in the context of legal positivism and I further render it problematic within the Critical Legal Studies that unmask and expose the processes of law’s legitimation in society. I give reasons for the need of applying the methods of the humanities for reaching an independent moral perspective that is not entirely a product of the legal system. I discuss the objections to the humanistic project so that to demonstrate their deficiencies and to reject them, and at the end to reinforce this project as a possible and meaningful moral critique of law.